377 The ban of tramadol and hazard prevention in cycling. (3rd March 2020) - Bigard, Xavier; Turin, Angeline; Salamin, Olivier; Faiss, Raphael; Daali, Youssef; Rudaz, Serge; Rossi, Francesca; Saugy, Martial
Abstract : Background: Tramadol is a synthetic opioid not banned by WADA, but included in the Monitoring Program since 2012. The prevalence of use of tramadol in competition was approximately 5% in cycling. These data clearly suggest that there was a misuse of tramadol in cycling. Opioids have several adverse effects, including nausea, dizziness and reduced vigilance. Such effects might be a potential cause of falls during races. Moreover, the psychoactive effects of tramadol are known to lead to abuse and then to drug dependence. Objective: In order to decrease the risk of falls and prevent the occurrence of opioid-related side effects, the UCI has decided to ban the use of tramadol in competition from the 1st March 2019. This regulation was part of a vast program of injury prevention in cycling, and was included in the UCI medical rules. Main outcome measurements: The tramadol controls are done in dried blood spots (DBS). The capillary blood is taken from a finger using a specific device that allows reliable collection (Hemaxis-DB10, DBS-System SA, Gland, Switzerland). DBS samples are sent to the reference laboratory in sealed bags through a reliable courier company. Tramadol analyses are performed by using the UHPLC-MS/MS technique. Positive results are based on the presence of the parent compound and its two main metabolites. The results are reviewed by an independent third entity, and sent to the UCI Medical Director. Positive controls are sanctioned with disqualification of the event and a fine. Results: As this summary is being written, 520 controls have been done in UCI-WorldTour races and World Championships. No positive results were reported. Conclusions: The ban on tramadol in cycling is a UCI medical regulation totally independent of the WADA rules, and supported by medical reasons intended to prevent the risks of injuries and opioid-related side effects. The introduction of the Tramadol-DBS tests has obviously a strong deterrent effect on its use in cycling.